Intra-G(1) arrest in response to UV irradiation in fission yeast - Nilssen, Esben A. (National Academy of Sciences, 2003)
G(1) is a crucial phase of cell growth because the decision to begin another mitotic cycle is made during this period. Occurrence of DNA damage in G(1) poses a particular challenge, because replication of damaged DNA can be deleterious and because no sister chromatid is present to provide a template for recombinational repair. We therefore have studied the response of Schizosaccharomyces pombe cells to UV irradiation in early G(1) phase. We find that irradiation results in delayed progression through G(1), as manifested most critically in the delayed formation of the pre-replication complex. This delay does not have the molecular hallmarks of known checkpoint responses: it is independent of the checkpoint proteins Rad3, Cds1, and Chk1 and does not elicit inhibitory phosphorylation of Cdc2. Irradiated cells eventually progress into S phase and arrest in early S by a rad3- and cds1-dependent mechanism, most likely the intra-S checkpoint. Caffeine alleviates both the intra-G(1)- and intra-S-phase delays. We suggest that intra-G(1) delay may be widely conserved and discuss significance and possible mechanisms.